2021
DOI: 10.33367/piaud.v1i2.1801
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Maze Kotaku untuk Menstimulasi Kemampuan Memecahkan Masalah pada Anak Usia 4-5 Tahun

Abstract: Tahapan berpikir pra-operasional merupakan saat anak-anak membutuhkan sebuah media pembelajaran yang dapat menggabungkan pola pikir sederhana terutama dalam kemampuan mencari solusi dari masalah yang dihadapi. Anak terbiasa dengan bimbingan dan pendampingan yang sangat ketat dari orang dewasa disekitarnya membuat tidak memiliki kebebasan menentukan pilihan sendiri. Permasalahan ini dihadapi oleh anak di lembaga PAUD Darussalam Jabon dari 13 anak capaian kognitif terkait kemampuan memecahkan masalah hanya 4 ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…From the results of research conducted by (Eka Saputri et al, 2024) it is concluded that children aged 4-5 years can benefit from the expressive language stimulation provided by the pop-up book five magic words. This pop-up book five magic words provides benefits felt by the child, including, the child is able to express simple words and sentences, express the child's feelings, easily understand the words greeting, excuse me, please, sorry, and thank you .…”
Section: Statistic Analysis Normality Test and Wilcoxon Testmentioning
confidence: 99%
“…From the results of research conducted by (Eka Saputri et al, 2024) it is concluded that children aged 4-5 years can benefit from the expressive language stimulation provided by the pop-up book five magic words. This pop-up book five magic words provides benefits felt by the child, including, the child is able to express simple words and sentences, express the child's feelings, easily understand the words greeting, excuse me, please, sorry, and thank you .…”
Section: Statistic Analysis Normality Test and Wilcoxon Testmentioning
confidence: 99%